Anxiety Over the Future: Cultural and Historical Insights into Technological Fears - Stoica, Victor (Technium Social Sciences Journal, 2024)
This study seeks to analyze how people perceive fear and risks differently today compared to how they viewed them in the past, elements that are closely related to technological development and its influence on everyday life, even if they have an impact at the micro or macro level. In this article we will analyze historical data to see how people perceived the utility and the risks associated with technological development in the past, such as the development of forging metal, the making of the wheel, the invention of the press or the engine. We will also analyze some more modern examples and we will end up talking about some recent technologies and what advantages and disadvantages they would present for modern society.